Pola Pikir Relatif (Relative-thinking) Siswa Kelas 5 dalam Menyelesaikan Masalah Kontekstual - Wisnu Siwi Satiti (JoEMS (Journal of Education and Management Studies), 2019)
Concept of proportions is essential for many educational topics. However, many students find it difficult to solve problems on proportion. The students often find it hard to determine an appropriate reasoning to be used in a certain situation, whether they should use absolute or relative thinking. Therefore, we need to design learnig activities that support the development of students’ relative thinking in solving problems on proportions. Due of that, we designed learning activities involving contextual problems which are based on the tenets of Realistic Mathematics Education (RME). The result of this study shows that contextual problems may promote students’ relative thinking in solving problems on proportion. Keywords: Relative thinking; Contextual problems; Proportion.